2023
DOI: 10.1097/hs9.0000000000000892
|View full text |Cite
|
Sign up to set email alerts
|

Definition and Prognostic Value of Ph-like and IKZF1plus Status in Children With Down Syndrome and B-cell Precursor Acute Lymphoblastic Leukemia

Abstract: Children with Down syndrome have an augmented risk for B-cell acute lymphoblastic leukemia (DS-ALL), which is associated with lower survival than in non-DS-ALL. It is known that cytogenetic abnormalities common in childhood ALL are less frequent in DS-ALL, while other genetic aberrancies (ie, CRLF2 overexpression and IKZF1 deletions) are increased. A possible cause for the lower survival of DS-ALL that we herewith evaluated for the first time was the incidence and prognostic value of the Philadelphia-like (Ph-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
0
0
Order By: Relevance
“…Buitenkamp T et al showed that DS-ALL patients had a similar frequency of IKZF1 deletions to that of high-risk (HR) non-DS-ALL patients (~30%) (81). Palmi C et al discovered that the IKZF1 plus feature in DS-ALL was 3 times more frequent than in non-DS-ALL (18% versus 6%), and IKZF1 plus patients had even worse outcome as well as higher relapse (82). Furthermore, they also found that the blasts of IKZF1 plus DS-ALL patients were particularly sensitive to drugs which had been described to be effective in Ph-like cases, such as HDAC inhibitors.…”
Section: Ikzf1 Alterations and Hereditary Leukemiamentioning
confidence: 99%
See 2 more Smart Citations
“…Buitenkamp T et al showed that DS-ALL patients had a similar frequency of IKZF1 deletions to that of high-risk (HR) non-DS-ALL patients (~30%) (81). Palmi C et al discovered that the IKZF1 plus feature in DS-ALL was 3 times more frequent than in non-DS-ALL (18% versus 6%), and IKZF1 plus patients had even worse outcome as well as higher relapse (82). Furthermore, they also found that the blasts of IKZF1 plus DS-ALL patients were particularly sensitive to drugs which had been described to be effective in Ph-like cases, such as HDAC inhibitors.…”
Section: Ikzf1 Alterations and Hereditary Leukemiamentioning
confidence: 99%
“…Song C et al demonstrated that TBB and CX-4945, different kinds of casein kinase II inhibitors, restored IKAROS activity and showed an antileukemia effect by inhibiting the transcription of the genes involved in the PI3K pathway (105). Palmi C et al studied some compounds in vitro cell culture that show one of histone deacetylase inhibitors, Givinostat, has the highest efficacy on IKZF1 plus blasts in comparison to controls (82). In the clinical setting, the direct targeting of IKZF1 to restore its function have not been yet.…”
Section: Treatment Of Bcp-all Patients Target To Transcriptional Regu...mentioning
confidence: 99%
See 1 more Smart Citation